2010
DOI: 10.1080/13548506.2010.482142
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a group cognitive-behavioural breathlessness intervention on health status, mood and hospital admissions in elderly patients with chronic obstructive pulmonary disease

Abstract: Non-pharmacological breathlessness interventions in lung cancer have proven beneficial. Breathlessness is also a major symptom in chronic obstructive pulmonary disease (COPD). This study measured the effectiveness of a non-exercise-based four-week cognitive-behavioural breathlessness intervention, delivered in a group setting for elderly patients with severe COPD. The results of the one-year feasibility study are presented. Patients with COPD were asked to complete the St. George's Respiratory Questionnaire an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 43 publications
1
31
0
1
Order By: Relevance
“…As an intervention, there are few research studies to demonstrate the benefits of activity pacing specifically, although there are many that propose its benefits as part of a programme of nonpharmacological interventions for the breathless patient [9,[25][26][27][28][29][30]. Much of the literature Creates positive-end expiratory pressure (PEEP) to maintain patency of unstable airways, improving expiratory airflow and therefore reducing dynamic hyperinflation [8,10].…”
Section: Activity Pacing and Energy Conservationmentioning
confidence: 98%
“…As an intervention, there are few research studies to demonstrate the benefits of activity pacing specifically, although there are many that propose its benefits as part of a programme of nonpharmacological interventions for the breathless patient [9,[25][26][27][28][29][30]. Much of the literature Creates positive-end expiratory pressure (PEEP) to maintain patency of unstable airways, improving expiratory airflow and therefore reducing dynamic hyperinflation [8,10].…”
Section: Activity Pacing and Energy Conservationmentioning
confidence: 98%
“…There appeared to be three general groups of adjunctive strategies: breathing training [64,66,70], psychological approaches [68,69] and electrophysical agents [67,71]; however, findings were inconsistent within these groups.…”
Section: Primary Studies Of Interventions For Relief Of Dyspnoeamentioning
confidence: 99%
“…63 There is preliminary evidence that cognitive behavioral therapy may improve depression and anxiety. 64,65 Additionally, several studies have demonstrated the utility of pulmonary rehabilitation in improving symptoms of depression and anxiety. 66 In the absence of COPD-specific data, it has been recommended that patients who have low BMI and/or treatment with corticosteroids should be screened for osteoporosis by DEXA scanning and serum 25-OH vitamin D levels.…”
Section: Functional and Cognitive Disability Among Persons With Advanmentioning
confidence: 99%